Study of electromagnetic spectrum from a focus science, technology and society - Moreno-Mediavilla, Daniel; Pascual López, Virginia; Palacios Ortega, Alicia; Pineros, V. (EDULEARN16: 8TH International conference on education and new learning technologies, 2020)
A proposal for classroom work, based on a Science Technology Society (STS) approach to developing content related to the electromagnetic spectrum is presented in this communication. It will analyze what the electromagnetic spectrum is, how it interacts with matter and which applications are more interesting and closer to the student. The methodology presented to develop this proposal, focuses on alternating lectures with the presentation and implementation of simple practice.
Keywords: electromagnetic spectrum; science; technology and society; learning difficulties; WOS(2)